Simulation and Implementation of Multiple Unipolar Stepper Motor Position Control in the Three Stepping Modes using Microcontroller - Ayman Y. Yousef; M. H. Mostafa (Institute of Advanced Engineering and Science, 2016)
This paper presents a multiple unipolar stepper motor position control system using microcontroller (MCU) in anticlockwise and clockwise directions. The open loop controller of the implemented position control system for the three stepping modes of operation has been designed and developed with three stepper motors and without position feedback. The MCU is programmed using flowcode software package to generate the pulse signals with the desired stepping sequences and step angles. These pulse signals are necessary to drive the three stepper motors in the three drive modes (wave-step, full-step, and Half-step) according to the control algorithm. Three devices of 8 Channel Darlington Driver (chip ULN2803) are used to drive the three stepper motors and provide them with the sufficient current. The position control system has been simulated using proteus design suite software package and the controller has been implemented using low cost PIC16F877A (MCU). A reliable and accurate position control of the stepper motor is achieved by this position control system.